The Effects of Foot Touch Therapy on Blood Pressure in Hypertension Patients in The Puskesmas Of Dlanggu Mojokerto - Yulianti, Indra; Mardiyana, Rina (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The results of the studyreveals that the systolic blood pressure increases by 13.6 mmHg and the diastolic decreases in diastolic blood pressure by 8.5 mmHg. The result showsp value 0.000 <α, and it is concluded that H0 is rejected and means that Foot Touch Therapy against blood pressure for patients with hypertension effectively reduces systolic blood pressure. The therapy model is considered good by 72.8%. The results of the analysis of the equivalence test in the diastolic variable group using the Levene's test obtained p value> α.It can be concluded that the data is homogeneous. The Ancova analysis results obtain F count 82.53 and p-value 0.000 <α, it can be concluded that H0 is rejected. It means that foottouch therapy against blood pressure in patients with hypertension effectively reduces diastolic blood pressure. The model of therapy is quite good by62%